Pembuatan Video Edukasi Vaksinasi Covid-19 Pada Civitas Akademika Universitas Muhammadiyah Mataram - Anna Pradiningsih; Mahacita Andanalusia; Baiq Leny Nopitasari; Baiq Nurbaety; Alvi Kusuma Wardani; Cyntiya Rahmawati (Universitas Muhammadiyah Semarang, 2021)
Vaccine is a biological product that used to stimulate the production of antibodies and provide immunity against infectious disease. In he beginning of 2021, Indonesia has started vaccination program for COVID-19. The main purpose of the program is to prevent the massive spread of corona virus, which has caused pandemic since December2019. There are some steps of vaccination program based on the community target. Muhammadiyah University of Mataram as a formal educational institution that gives public service to society is included in the second step of vaccination. However, the variety of field at the institution causes the knowledge differences about vaccine. Therefore, education to help civitas academics to understand more about vaccine was needed. Education was done by audio visual method or video. The videos were made with two language, Indonesian and English. Some contents that included in the video were vaccine definition, type of vaccine, vaccine’s mechanism of action, vaccine’s benefit, COVID-19 vaccine, the possible effects after getting COVID-19 vaccine and how to overcome them. The videos was uploaded in the internet and distributed online to che civitas academics. Through this video, it is hoped that the civitas academics can understand the importance of their participation in COVID-19 vaccine.